The incidence of early postoperative complications after spinal anaesthesia - Kamenik, Mirt; Horvat, Smiljana (Acta Medico-Biotechnica, 2021)
Purpose: The purpose of our study was to gather data about the incidence of early post-operative complications after spinal anaesthesia at the University Medical Centre Maribor. We were interested in the impact of gender, age, and a number of attempts to insert the spinal needle on the incidence of these complications. Methods. We studied 90 patients who underwent a surgical procedure involving the lower extremities under spinal anaesthesia. Twenty-four to 72 hours after spinal anaesthesia, we collected data about early complications from a questionnaire and data about technical difficulties associated with the spinal puncture. Results. Among 90 patients, 23 (25.5 %) reported no complications. The most common complication was tingling in the lower extremities (43 %) and nausea (31 %). Back pain was present in 21 % of patients, 18 % had headaches, 19 % had vertigo, and 13 % had double vision. Headache, diplopia, and dizziness were more common in women, while backache was more common in men. There was a tendency towards an increase in the incidence of complications with age, especially diplopia, vomiting, and dizziness. The incidence of complications was also higher in patients requiring > 3 attempts for effective spinal puncture Conclusion. Our study showed that complications after spinal anaesthesia occur more often in female patients and in patients > 55 years of age. The most common complications were tingling in the lower extremities, dizziness, and nausea. The incidence of complications was higher in patients requiring > 3 attempts for effective spinal puncture.